Peran pembelajaran Pancasila di LPTK untuk meningkatkan konsep diri akademik dalam mengantisipasi dehumanisasi pendidikan pada semester II Program Studi Pendidikan Agama Islam Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto - Ubaidillah, Aan Eko Khusni (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
This study aims to find out how the role of learning Pancasila in LPTK to improve academic self-concept in anticipating the dehumanization of education in the second semester of Islamic Higher Education Studies Program Tarbiyah High School Raden Wijaya Mojokerto. This research includes field research, qualitative models, case studies. Determination of purposive sample with snow balling characteristics to obtain variation and extend information so that it can be contrasted with other information. Observation Data Collection Methods, Interviews and Documentation. Data Analysis uses analytical descriptive by doing Triangulation checking the validity of other source data outside the existing data as a comparison to obtain data unity. The result of the research shows: 1) the implementation of Pancasila Learning besides emphasizing the cognitive aspect has also emphasized the affective and psychomotor aspect, it is realized in one of the learning method using problem solving method, beside that the Institution also support with national and religious activities. 2) The role of learning Pancasila directly is still less realized in the real level in the field, but at least the initial capital to be able to have good behavior, of course the next expectation is the existence of good behavior then dehumanisasi education on students can be suppressed, to further maximize the results Learning required student awareness, cooperation between lecturers, lecturers and stakeholders. 3) There are several inhibiting factors, namely institutional policy factors, family factors, student behavior starting at home, other factors are the student's own personal which is difficult to change and improve through formal education media. Factor of learning and education second after parent. And the last factor is the environment, it refers to the role of society.